Monitoring in semiology and semio-techniques for nursing: an experience story - Vilani Medeiros Araújo Nunes (Universidade Federal de Santa Maria, 2012)
Objective: to report the experience of nursing students on performance of their monitoring activities in the discipline semiotics and semiology to nursing at an institution of higher education in Natal, Rio Grande do Norte, in the period between the months of September 2009 to September 2010. Method: the activities were performed in the nursing laboratory and carried out in two ways: first, there was monitoring the monitors, along with teachers of the practical lessons of discipline and, second, the monitors performed the orientation activities for students who were attending the course. Results: monitoring provides a differentiated experience to the student who opts for it, given the many experiences that can be experienced in its scope. Conclusions: through this activity, monitors actions developed teaching, research and extension that allowed the consolidation of knowledge